Isolated Aortic Valve Replacement: Early Results from a 16-Year Experience - Selman Dumani; Ermal Likaj; Saimir Kuci; Laureta Dibra; Fjorba Mana; Devis Pellumbi; Alfred Ibrahimi; Stavri Llazo; Edlira Rruci; Ervin Bejko; Aferdita Veseli; Andi Kacani; et al. (Albanian Journal of Trauma and Emergency Surgery, 2025)
Background: Aortic valve replacement (AVR) has been a routine procedure since the introduction of heart valve prostheses in the late 1960s and early 1970s. It is the most commonly performed heart valve surgery in cardiac surgical practice.